A Study on Constraints of Ericulture in Dhemaji District of Assam (Indian Journal of Extension Education, 2022)
Sericulture might be considered as an important area for uplifting the economy of rural masses of Assam as the nature has endowed with favorable climatic and environmental conditions for various silk producing worms and their food plants. The research study was undertaken in the purposively selected Dhemaji districts of Assam during the year 2022 with the objectives to study profile characteristics of Eri rearers and to explore the problems faced by them. A total of 120 farmers were selected as respondents and data were collected by following simple random sampling technique by the personal interview method using standardized structured interview schedule. Constraints faced by the Eri silkworm rearers were majorly categorized into five broad categories, viz., personal problem, non-availability of resources, problems during rearing of silkworm, marketing problems and problems related to post cocoon sector of sericulture Appropriate statistical tools viz. frequency, percentage, mean was employed to analyze the data. Findings revealed that majority of the respondents termed “lack of capital” (2.86), “unavailability of rearing equipment” (2.66), “could not get seed in time” (2.88), “involvement of middle men” (2.75) and “lack of availability of spinning machine” (2.73) as the most serious problem under each category.